Risk Management Strategies for Waste-to-Energy Projects Utilizing BOT Models - Jie, Xinggang; Jie, Yinggang (International Journal of Natural Resources and Environmental Studies, 2024)
Since the 1990s, with the implementation of the reform and opening up policy, the rapid development of China’s economy, the progress of urbanization is getting faster and faster, and as one of the urban wastes, the treatment of domestic waste has also attracted more and more attention. The municipal solid waste incineration treatment, and the heat generated after combustion is used to generate electricity, referred to as "garbage incineration power generation", because this way can make the waste to reduce, harmless, and can be converted into part of the electricity, because it is widely used in the treatment of municipal solid waste by local governments. Due to the shortage of government funds, most domestic waste incineration projects are implemented in BOT mode. Waste incineration power generation projects are often a large investment, for investors, the recovery period is long, the technical requirements are high, the investment agreement signed with the government is also very complex, coupled with the imperfect supporting laws and policies in China, so that the process of waste incineration power generation projects have many problems and risks, through the operation, construction, investment and other links. Based on the theoretical content of risk management in project management and combined with practical cases, this paper puts forward countermeasures and suggestions for important risks in the project, so as to analyze and discuss the risks of garbage incineration BOT project. Firstly, this paper investigates and collates the research situation of relevant projects at home and abroad, and systematically summarizes the project research results from three aspects, namely, BOT risk management of waste incineration power generation projects, BOT model of projects and BOT project risk research. Secondly, the multi-case study method was used to analyze the risks of 3 typical waste-to-power generation BOT projects, collect risk factors, construct risk aggregation, and summarize 5 types of key risks and 14 kinds of risks. Then, according to the BOT agreement signed with the government side, the specific risk management method is proposed. The goal of this study is the LF waste incineration power generation project. The author participated in the project and identified and evaluated the project risks through risk list and hierarchical analysis, so as to find out the main risks in the project such as government risk, public opinion risk, completion risk and operational risk. In addition, in combination with the project risk, specific risk coping strategies are proposed according to the risk coping strategies proposed in the paper and the actual situation of the project, so as to reduce the degree of project risk and reduce risk losses. For other similar projects in China, there is reference and reference significance and value.